Decentralised secure handover in IMS–based networks. (27th August 2012) - Chiang, Wei–Kuo; Kuo, Po–Chiang
This paper proposes a decentralised secure handover scheme for service continuity in IP Multimedia Subsystem (IMS)–based networks: Decentralised Service Continuity (DSC). The novelty of the DSC is that the Proxy Call and Session Control Function (P–CSCF) in IMS is enhanced as a distributed Application Server (AS) with third–party call control (3PCC) for handling the handover. Moreover, the DSC integrates a secure context transfer mechanism to the P–CSCF to get the context information of a newly attached User Equipment (UE) and guarantee the confidentiality and the integrity. The DSC could shorten the IMS transmission latency significantly and reduce UE power consumption, as compared with the standard IMS–based service continuity and the Mid–Session Macro–Mobility (MSM).